Regional History of Teaching in Personal Funds of Ural Teachers (on Material of 1920-1930-ies) - E. V. Protasova (Научный диалог)
The publication is a part of the research work on the history of pedagogy and childhood of the 20th century on the materials of personal funds of Ural teachers. The relevance of the study of the regional history of teaching in its relationship with the phenomenon of childhood is determined by the lack of interdisciplinary comprehensive analysis of the problem. The main directions of development of educational practice in the 1920-1930-ies are revealed. Biographical materials and memoirs of Ural teachers about the organization of the first Soviet schools, skill of teachers, daily life of people in a critical historical era are presented. Some features of the solution of actual problems of implementation of universal education and literacy of the population are shown. Elements of pedagogical experience on creation of cultural space of the childhood and organizational forms of realization of this experience in educational institutions are described. The contribution of teachers in the formation of the school in the Soviet period is mentioned. The information about selflessness of the Ural teachers, contributing to the study of pedagogical phenomena in the local-territorial aspect, is given. The possibilities of personal funds of Ural teachers to recreate the little-studied subjects of the history of the region on the basis of documents of personal origin are shown.